Effects of Extreme Temperature on Airway Smooth Muscle Cell Death - DoHarris, Lindsay E. (My University, 2012)
Bronchial thermoplasty has recently been FDA approved as a novel therapy for use on adults suffering from severe asthma. The procedure uses radiofrequency energy to heat the airways to 65°C for 10 s. This has been shown in dogs to lead to a reduction of airway smooth muscle mass and in humans to improve quality of life and asthma control. Early cellular reactions to this treatment are unclear; as well, there is limited information regarding thermal sensitivity of airway smooth muscle when exposed to extreme temperatures (50-65°C). We examined the cellular impact of bronchial thermoplasty by investigating the response of airway smooth muscle to heat by immersing bovine tracheal strips and bronchial segments in heated Krebs. We confirmed dramatically decreased functionality over the temperature range 50-60°C at 1 h and 24 h in all tissues. TUNEL analysis noted significant cell death in all tissues heated to 65°C and limited cell death in bronchial tissues treated with <55°C. Immunohistochemical analysis showed an effect of temperature on caspase 3 activation in bronchi; tracheal strips demonstrated co-localization of caspase 3 and TUNEL at 55°C but not 65°C. These data suggests that cell death of airway smooth muscle contributes to the cellular effects observed following heating to 65°C; at lower temperatures, cell death may be limited. We conclude that bronchial thermoplasty (heat treatment to 65°C for ~30 seconds) leads to a number of structural and functional changes in the airway smooth muscle, which culminate in marked loss of function and cell death.
Keywords: Asthma; Airway Smooth Muscle; Bronchial Thermoplasty; Heat; Cell Death; Medical Molecular Biology; Medical Molecular Biology